Business Strategy, Audit Quality, And Independent Commissioners on Earnings Management: The Moderating Role of Media Coverage - Eko Widianarko KUSNADI; Nurul HIDAYAH (Journal of Governance, Taxation and Auditing, 2026)
This study investigates the influence of business strategy, external audit quality, and independent commissioners on earnings management, with particular attention to the moderating effect of media coverage. By applying purposive sampling, this study obtained 224 firm-year observations from 56 consumer non-cyclical firms listed on the Indonesia Stock Exchange over the period 2021–2024. This study conducted the data analysis using panel data regression and moderated regression analysis (MRA). The results indicate that business strategy has a significant effect on earnings management, while external audit quality does not. This study also discovered that independent commissioners significantly impact earnings management. The moderation test reveals that media coverage has no significant moderating effect on the relationship between business strategy or external audit quality and earnings management; however, it strengthens the monitoring function of independent commissioners in mitigating earnings management. These findings imply that external monitoring in the form of media exposure reinforces the role of independent commissioners as an internal governance mechanism, thereby encouraging higher-quality financial reporting practices and supporting effective corporate governance.